2018
DOI: 10.1016/j.bjorl.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

25 (OH) D3 levels, incidence and recurrence of different clinical forms of benig paroxysmal positional vertigo

Abstract: There were no significant differences in the vitamin D3 serum level in patients with and without recurrence. The study showed a low level of serum vitamin D3 in most patients, indicating the need for supplemental therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 31 publications
1
20
0
3
Order By: Relevance
“…After further evaluation of remaining 99 full-text studies, sixty eligible studies with 36 646 patients were finally included in this meta-analysis. 9-12,13,16,18,22-78 A PRISMA flow diagram were presented to describe the detail selection process (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…After further evaluation of remaining 99 full-text studies, sixty eligible studies with 36 646 patients were finally included in this meta-analysis. 9-12,13,16,18,22-78 A PRISMA flow diagram were presented to describe the detail selection process (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, it has been proposed that a third disorder, namely vitamin D deficiency, may be contributing to the development of both conditions 6,7 and we have proposed a mechanistic conceptual model for this relationship 8 . In addition to its well-known roles in bone biology and osteoporosis 9 , decreased vitamin D has also been associated with a variety of other conditions 9 , most recently idiopathic BPPV 4,68,1014 , particularly in the recurrent disease 6,10,15,16 . It has been argued that the prevalence of osteoporosis and vitamin D deficiency in the general population is high and therefore that the coexistence of BPPV with osteoporosis and vitamin D deficiency may be purely coincidental 17 .…”
Section: Introductionmentioning
confidence: 99%
“…[34] In severe vitamin D deficiencies, improvement of serum vitamin D levels was shown to diminish the recurrence rate of BPPV. [32] On the contrary, Maslovara et al [35] indicated the need for supplemental therapy due to a low level of serum vitamin D3 in most BPPV patients participating in their study, although no significant difference was shown in vitamin D3 levels in patients with and without recurrence. Future studies should be focused on clarifying the effect of vitamin D supplementation in decreasing recurrence rates in patients with recurrent BPPV.…”
Section: Vitamin D and Otolaryngological Diseasesmentioning
confidence: 87%